Identifying ligands of the C-terminal domain of cardiac expressed connexin 40 and assessing its involvement in cardiac conduction disease - Keyser, Rowena J. (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScMedSc (Biomedical Sciences. Molecular Biology and Human Genetics. Medical Biochemistry))--University of Stellenbosch, 2007.